2016
DOI: 10.1186/s12866-016-0657-z
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in taxonomic and functional microbial diversity with agriculture: How fragile is the Brazilian Cerrado?

Abstract: BackgroundThe Cerrado—an edaphic type of savannah— comprises the second largest biome of the Brazilian territory and is the main area for grain production in the country, but information about the impact of land conversion to agriculture on microbial diversity is still scarce. We used a shotgun metagenomic approach to compare undisturbed (native) soil and soils cropped for 23 years with soybean/maize under conservation tillage—“no-till” (NT)—and conventional tillage (CT) systems in the Cerrado biome.ResultsSoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 89 publications
4
56
0
1
Order By: Relevance
“…Conversion of forest to agriculture, pasture or deforestation all lead to significant changes in the abundance of functional genes associated with respiration (Mendes et al, 2015). In regard to agricultural management practices, the relative abundance of respiratory functional genes increases in no tillage cropping systems compared to native ecosystem (Souza et al, 2016). However, where SOM and MBC had significantly decreased under 23 years of conventional tillage, decreases in the relative abundance of respiratory functional genes compared to native ecosystem occurred (Souza et al, 2016).…”
Section: Physiological Differences In Electron Transport Chainsmentioning
confidence: 94%
See 1 more Smart Citation
“…Conversion of forest to agriculture, pasture or deforestation all lead to significant changes in the abundance of functional genes associated with respiration (Mendes et al, 2015). In regard to agricultural management practices, the relative abundance of respiratory functional genes increases in no tillage cropping systems compared to native ecosystem (Souza et al, 2016). However, where SOM and MBC had significantly decreased under 23 years of conventional tillage, decreases in the relative abundance of respiratory functional genes compared to native ecosystem occurred (Souza et al, 2016).…”
Section: Physiological Differences In Electron Transport Chainsmentioning
confidence: 94%
“…In regard to agricultural management practices, the relative abundance of respiratory functional genes increases in no tillage cropping systems compared to native ecosystem (Souza et al, 2016). However, where SOM and MBC had significantly decreased under 23 years of conventional tillage, decreases in the relative abundance of respiratory functional genes compared to native ecosystem occurred (Souza et al, 2016). Increasing N fertilisation (across gradients of 0e291 kg N ha À1 year À1 ) increases the relative abundance of ubiquinonecytochrome reductase complexes and F 0 F 1 ATP synthase (Fierer et al, 2012), similar to shifts observed in Table 2.…”
Section: Physiological Differences In Electron Transport Chainsmentioning
confidence: 99%
“…Navarrete et al [7] reported taxonomic and functional adaptations in soil microbiome after deforestation in the Amazon region and these adaptations typically result in increased soil fertility. Other agricultural practices, such as logging [43], tillage [44] and cropping systems [45,46], also play roles in effecting structural and functional changes in soil microbiome that lead to changes in soil functions. As many of the discussed agricultural management practices have been implemented for decades with success, recent efforts in understanding their effects on soil microbiota composition would enable rational engineering of the soil microbiome to optimize these practices for improved crops.…”
Section: Engineering Of Soil Microbiomementioning
confidence: 99%
“…Agricultural management Soil Organic farming, changing land usage, logging, tillage, cropping [7,[41][42][43][44][45][46] Improve soil fertility • Alter structure and function of soil microbiome;…”
Section: Examples Purposes Remarksmentioning
confidence: 99%
“…The Alphaproteobacteria clade of balance 'n138' also possesses a number of Sphingomonadales ASVs. BothSphingomonadales and Rhizobiales have been shown to increase in relative abundance when land is used for agriculture(Souza et al 2016) and Sphingomonadales was among a number of groups shown to previously increase in relative abundance in the sweetpotato rhizosphere(Marques et al 2014) .…”
mentioning
confidence: 99%